2016
DOI: 10.1093/jxb/erw202
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress response triggers activation of the jasmonate signaling pathway leading to inhibition of cell elongation in Arabidopsis primary root

Abstract: HighlightThis study identifies that salt-inhibited root growth partially involves the activation of the jasmonate signaling pathway in Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 58 publications
8
108
0
Order By: Relevance
“…Nevertheless, the underlying mechanisms by which JA synthesis is controlled by ABA are not well understood. During abiotic stress, rising ABA levels induce JA synthesis, which synergistically optimizes plant abiotic defenses by altering the plant transcriptome, possibly facilitating stomata closure, inhibiting cell division, and epigenetically modifying defense genes during dehydration responses (Murata et al, 2015;Riemann et al, 2015;Liu et al, 2016;Valenzuela et al, 2016). A basic-helix-loop-helix transcription factor MYC2 plays roles in both JA and ABA signaling and has been proposed as one of the factors linking ABA and JA signaling (Kazan and Manners, 2013;Aleman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the underlying mechanisms by which JA synthesis is controlled by ABA are not well understood. During abiotic stress, rising ABA levels induce JA synthesis, which synergistically optimizes plant abiotic defenses by altering the plant transcriptome, possibly facilitating stomata closure, inhibiting cell division, and epigenetically modifying defense genes during dehydration responses (Murata et al, 2015;Riemann et al, 2015;Liu et al, 2016;Valenzuela et al, 2016). A basic-helix-loop-helix transcription factor MYC2 plays roles in both JA and ABA signaling and has been proposed as one of the factors linking ABA and JA signaling (Kazan and Manners, 2013;Aleman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Phytohormones are the key regulators of plant growth and development and act as mediators of environmental stress responses [5]. Plenty study showed that jasmonic acid (JA) was involved in various processes such as plant growth, reproductive output as well as stress resistance [12,13]. Our study showed that two genes from ZQUA44 encoding lipoxygenase (LOX), an important enzyme catalyzing linolenic acid into [17].…”
Section: Discussionmentioning
confidence: 85%
“…A recent study also shows that the effect of salt on inhibiting root growth is mediated by JA [16]. Therefore, we wanted to know if OsWRKY42 enhances salt stress tolerance by modulating expression of genes in the JA response pathway.…”
Section: Resultsmentioning
confidence: 99%